PENGARUH LITERASI KEUANGAN, INKLUSI KEUANGAN TERHADAP KINERJA UMKM - Lindananty Lindananty; Elizabeth Angel Christina (STKIP PGRI TULUNGAGUNG, 2022)
The purpose of this study was examine the impact of financial literacy, financial inclusion and financial planning on the performance of MSMEs. The research ws conductes on 45repondents fromMSMEs at the Sanan Chips and Tempe Industry Community Centre. This study uses primary data from questionnaires. The results of the study are that financial has no effect on the MSMEs performance, but financial inclusion have a positive effect on the performance of MSMEs